The Impact of Macroeconomic Policieson the Level of Taxation (andon the Fiscal Balance) in Developing Countries - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1988)
In recent years the level of taxation of many developing countries has changed dramatically over relatively short periods. These changes are too large and too sudden to attribute fully to a deterioration in tax administration or to changes in the traditional determinants of tax levels. The paper argues that they should be attributed mostly to macroeconomic policies. The paper discusses the connection between tax levels and (a) the real value of the official exchange rate, (b) import substitution policies, (c) trade liberalization, (d) inflation, (e) public debt, (f) financial policies. The paper concludes that more attention should be paid to those relationships and that tax reform should aim at neutralizing some of these effects.